An approach to the Da Vinci and Vesalio's art: contribution to anatomical teaching - Greta Margarita Arrechea García; Adys Castro Berberena (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2023)
From the most remote Jurassic time, the Greek civilization, the Claudio Galen's ancient Rome, the Middle Ages and contemporary Renaissance, the Harvey and Malpighi's modern age, as well as the 19th century considered as the "modern period" of Anatomy, where Galen's descriptive vision is expanded, and Vesalius' architectural vision, have been the arts an important factor to take into account in the science development. Leonardo da Vinci and Andrés Vesalio are considered great anatomists, who contributed the most with their art to its development. The current influence of the successful contributions of these two universal men in the anatomy rooms are considered as essential ideas, since the classical anatomy teaching has been carried out in all the world's universities by means of cadaver dissection methods, established methodology in the anatomical environment that should not be dismissed or replaced, if not complemented with the new current resources.